Pengindraan Hoaks Bagi Pemilih Pemula: Pendidikan Anti-Hoaks Sebagai Langkah Awal Menuju Pemilu Sehat 2024 - Kurlillah, Anis; Zubir; Alfian; Fakhrizal bin Mustafa; Munadiati (Pencerah, 2024)
This study projected the action of political literacy and promoting the ability to discern hoaxes among first-time voters during the 2024 election by instituting an anti-hoax education initiative. The research employed a socialization approach employing interpersonal communication (AKP) techniques. One hundred students enrolled in semesters 1 to 4 at the Faculty of Education and Islamic Studies (FEBI) of Langsa State Islamic University (IAIN) constituted the participant pool, organized into 10 small groups. Each group featured a designated facilitator tasked with guiding discussions focused on the identification of hoaxes in electoral contexts. The instructional materials encompassed topics such as electoral processes, the democratic system, hoax detection strategies, and penalties for disseminating hoaxes. The study's outcomes revealed a favorable response from first-time voters and a noteworthy transformation in their comprehension of hoaxes. These conclusions were drawn from the evaluation outcomes and responses to both pre- and post-tests administered to all participants. The implications of these findings underscore the significance of anti-hoax education as an initial stride toward cultivating astute and critical first-time voters in the context of elections. This investigation contributes to the advancement of analogous educational models and the establishment of more robust election procedures in subsequent occurrences